How Public is Public Law? The Current State of Open Access to Administrative Court Judgments. - Hoadley, Daniel; Tomlinson, Joe; Nemsic, Editha; Somers-Joce, Cassandra (Judicial Review, 2022)
Judicial review judgments available on BAILII.a [1] HT <thead valign="bottom"> Year Total number of judgments on vLex Total number of judgments on BAILII Number of judgments on vLex and BAILII Number of judgments only available on vLex Number of judgments only available on BAILII % of judgments on vLex and BAILII % of judgments only available on vLex </thead> 2015 1,303 7 There are now multiple sources for free, public access to court judgment publications, of which The British and Irish Legal Information Institute (BAILII) is the largest. In order to test whether a given judgment in our dataset was available on BAILII, we took the neutral citation assigned to the judgment[5] and used it to construct the link to the corresponding judgment on BAILII.[6] We wrote code that visited the constructed BAILII link and checked the resulting webpage for the presence of a message BAILII uses to tell its users that the judgment they are looking for was not found. While BAILII provides free access for the public to a significant number of judicial review judgments through its website, the BAILII database is not comprehensive.